Foreign culture influence youth identity: a study towards the influence in entertainment among FSPPP students at UiTM Samarahan Campus 2 / Nur Azimah Ahmad Beduwi and Puteri Auji Afiqah Megat Sabri - Ahmad Beduwi, Nur Azimah; Megat Sabri, Puteri Auji Afiqah (2014)
Youth in Malaysian context is defined as young people with the age of 15 - 40 (Ministry of Youth and Sport). Youth nowadays many has been influenced by the foreign culture whether positively or negatively. It is important for us to know about the influence of foreign culture, especially when the influence is negative towards the youth. This is because, when we know about or what type of negative influence that surrounding the youth, we can help in recommending suitable solutions as to solve or at least handle the problems of negative influence correctly.